"CHARACTERISTICS OF SPEECH AND COMMUNICATION SKILLS REGARDING GENDER DIFFERENCES" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the similar and different aspects of the process of communication and communication between men and women, as well as the importance of its role in society, are highlighted in this article.